DETEKSI OBJEK BERGERAK BERBASIS WARNA DENGAN METODE KONTUR MOMEN MENGGUNAKAN OPENCV 2.4.4 - , SHARAH PUTRI NURLINDA PRADANA; , Isnan Nur Rifaâi, S.Si, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Currently the use of image processing alredy widely use one of them is image processing for moving object. This system works to detec moving object in video real time. In this process needs the right system in order to detec objects well, ie with moment contour method using digital image technology. In this research the problem traying to be slove by detecting the edge of objects and contras color difference between the object and background, and object detection with HSV color. Then after the color of object detected it will be object position detection with momen contour method. Making the system using mini-PC and OpenCV as image processing system, the considation of this system can be further developed. Result from this research is a prothotype/model moving object detection based on color system are manifested in the form of software that implanted in yhe mini-PC. The test system is made by analyzing the video real time. The test result with distance variation the minimum distance is 0 cm and maximum is 30 cm, and then make line shape in accordance with the movement of the object.